A comparative bacteriological study of bottled drinking water In Nigeria - Philip Ifesinachi Anochie; Anthony Chidiebere Onyeozirila; Edwina Chinwe Onyeneke (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
Bacteriological examination of six brands of bottled drinking water samples produced by different bottled water producers in Nigeria was carried out to compare their bacterial quality. The bottled drinking water were bought from various sales outlets in Nigeria. The biochemical characteristics of the isolates and the sugar fermentation reactions of the isolates were studied. Results of the bacteriological examination showed varied degrees of bacterial load. Causes of contamination of the bottled drinking water and recommendations for improving their microbial quality were also highlighted.